The Effectiveness of Arranging Word Game In Teaching Grammar: An Evidence From VIII Grade Students of SMPN 2 Simpang Alahan Mati, Indonesia - Yona Meidiastuti; Loli Safitri (Journal of English as A Foreign Language Teaching and Research, 2021)
The aim of this research was to know how the students’ ability in arranging word into a sentence of simple present tense and effectiveness of Arranging Word Game in teaching simple present tense at VIII Grade Students of SMPN 2 Simpang Alahan Mati. The researcher found some problems that related to arranging word game which was used by English teacher. The first problem was English teacher has been applied and used Arranging Word Game in teaching simple present tense, but some students still had difficulties in arranging word into a sentence. The second problem was some students often forgot with the structure of the sentence which was taught before such as the structure of simple present tense and the students’ mark was somewhat varied which 65% of the students were considered to have poor achievement. The third problem was some students still could not make sentence such as arranging word into a good sentence and could not understand the material well. This research used a descriptive quantitative research. The population of this research was all students at VIII Grade of SMP N 2 Simpang Alahan Mati where it consisted of two classes which were VIII.1 and VIII.2. In this research, the researcher used total sampling as a sampling technique and the total of sample was 65 students of VIII Grade students. The instruments that were used in this research were test and questionnaire. Based the result of this research, it was concluded that students’ ability in mastering simple present tense at VIII Grade Students of SMPN 2 Simpang Alahan Mati was very good category where the mean of students’ test result was 88,06 on the rating scale 80-100 which was on the very good category. Furthermore, Arranging Word game was effective to be used in teaching simple present tense at VIII Grade Student of SMPN 2 Simpang Alahan Mati where it was gotten from the mean data percentage of students’ questionnaire result which was 77,06% on the percentage of rating scale on 72-89% which it was effective on rating quality.